Origins, organisation and significance of the Festival of Britain 1951 - Ebong, Inyang Isola Ime (University of Edinburgh, 1986)
This Thesis sets out to examine an event which has been little documented and accordingly as comprehensive a view as is possible has been adopted. It will embrace an analysis of the origins of the Festival of Britain, its organisation, the content of its major exhibitions and events and finally, the impact and significance of what has turned out to be the last major exhibition to be held in post-war Britain. The content of the individual chapters is as follows: Chapter 1: The idea of staging a first category international exhibition, the movement away from this idea towards a national exhibition and the eventual emergence of the Festival of Britain concept. Chapter 2: The setting up of the Festival Organisation and the selection of its personnel; the influence of such selection on the Festival's aims and content. Chapter 3: The search for acceptable sites for the component exhibitions and the Organisation's plans to give the Festival a nationwide character. Chapter 4: The financial arrangements with particular reference to the economic climate of the time. The two major problems faced by the Organisation in their financial strategy occasioned by the London County Council claims for compensation and the difficulties sustained by the Festival Gardens Company Ltd. Chapter 5: The publicity arrangements. A general description of the Festival elements and the official opening ceremony. Chapter 6: A description of the South Bank site with particular reference to the architecture and design of selected pavilions as representative of certain architectural trends exemplified in pre-war exhibitions and elsewhere. Critical reaction and assessment of the contribution to British architecture of the South Bank. Chapter 7: A survey of the other London exhibitions and of the Pleasure Gardens at Battersea. Chapter 8: Festival activities throughout the rest of the United Kingdom. Chapter 9: Art and Design in the Festival with reference to the growth and development of the Arts Council and the Council of Industrial Design. Chapter 10: The argument for the Festival's opening to be extended; the dismantling of exhibition material; the closing ceremony. An assessment of the general impact and significance of the Festival.
The origins, organisation and significance of the Festival of Britain 1951
Keywords: History